PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA POKOK BAHASAN JURNAL PENYESUAIAN PERUSAHAAN JASA KELAS XI AKUNTANSI DAN KEUANGAN LEMBAGA SMK NEGERI 4 LAHAT - Anggreni Astrilova (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this study was to find out whether applying the problem-based learning model can improve student learning outcomes on the subject of adjusting journals of class XI accounting and financial service companies at SMK Negeri 4 Lahat. The subjects of this study were students of class XI at SMK Negeri 4 Lahat in the 2020/2021 academic year in the subject of practicum accounting for service companies, trade and manufacturing. With a sample of 26 people. In its implementation, each cycle is divided into 4 stages, namely planning the action, implementing the action, observing and interpreting it as well as analyzing and reflecting. The evaluation assessment during the first cycle of students who obtained a score above the KKM was 15 people (65.22%) with a class average of 73.04%. While the evaluation score in cycle II of students who obtained a score above the KKM was 21 people (91.30%) with a class average of 83.91%. In the second cycle the learning outcomes of students increased with a percentage of 91.30% completeness. This is based on the minimum completeness criteria (KKM) that have been fulfilled, namely 75. Based on the learning outcomes of cycle II students are easier to understand the learning material, this is evidenced by the increased learning outcomes of students. In terms of attitude, the application of this learning model provides positive improvements in students.